Tata Kelola Badan Usaha Milik Desa untuk Meningkatkan Pendapatan Asli Desa: Studi pada Bumdes Ngudi Raharjo Desa Girikulon, Kabupaten Magelang - Yusna Hidayat (Universitas Warmadewa, 2023)
This research study aims to analyze the Governance of a Ngudi Raharjo Village-Owned Enterprise to Increase the Original Income of Girikulon Village, Secang District, Magelang Regency. This study collected data through observation, interviews, and documentation using qualitative methods to describe and explain the management of the Ngudi Raharjo BUMDes. The results of this study indicate that the management of the Ngudi Rahardjo BUMDes to build Girikulon Village, Secang District, Magelang Regency is still not optimal. This is caused by several factors, including the human implementers caused by the low level of formal education in Girikulon Village and then the equipment factor caused by the lack of facilities and infrastructure at the Ngudi Raharjo BUMDes. In BUMDes Ngudi Rahardjo itself, there is positive community participation in a number of areas, financial management and organizational management.